Educational Background Analysis of CEOs of Large Indonesian Listed Companies - Aditya Andika; Claudia F. Susilo; Jennifer (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Education is an important factor in determining whether a person is suitable to become a CEO or not. Researches and surveys around the world has shown that CEOs of large companies are highly educated. However, there were not many detailed research regarding the education background of CEOs of large companies in Indonesia. Therefore, this study focused on analyzing the educational background of CEOs of Large Listed Companies in Indonesia. This study analyzed the educational background of the CEOs of 50 largest listed companies based on market capitalization. The names and the educational background of the CEOs was acquired through the Indonesian Stock Exchange website, Wall Street Journal website, LinkedIn, QS World University Rankings website, and Google. The main purpose of this study is to give insights to young Indonesians who are aspiring to become future CEOs of large listed companies regarding the ideal education degrees that they should strive to acquire in order to achieve their goals.This study found that the ideal education profile of future CEO is an overseas master or doctoral graduate in business-related fields from a university located in the USA, Australia, or UK that is listed in the QS World University Rankings.